South Africa’s challenges pertaining to mine closure — development and implementation of regional mining and closure strategies - van Tonder, DM; Coetzee, H; Esterhuyse, S; Strachan, L; Wade, P; Mudau, S (Mine Closure 2009: Fourth International Conference on Mine Closure, 2009)
Following the World Summit on Sustainable Development in 2002, the South African Department of Minerals and Energy (DME) initiated the “Sustainable Development through Mining” (SDM) programme to assist in the development of a strategic framework for sustainable development in the minerals and mining sector. This initiative supported a variety of projects including a project specifically orientated towards integrated regional mine closure and its implications. This paper focuses on the increasingly challenging environment of changing community expectations, stricter regulatory controls and greater public scrutiny in areas of cumulative, interconnected, or multi-mine, and/or an integrated environmental and socio-economic impact at a regional level. The paper discusses the challenges in the development and implementation of the concept of regional mine closure strategies, as support to further policy and legislative interventions in South Africa, and outlines proposed strategies to address these challenges. Regional closure strategies aim to provide a framework within which mines can develop closure plans that address broader development priorities as well as possible cumulative impacts of a number of mines, taking into consideration socio- economic and environmental issues on a regional basis. A strategic framework was developed for the Witwatersrand gold mining region within which individual mines will be able to plan for mine closure. In order for the strategy to be implemented there are a number of key success factors. These include issues around closure planning, buy-in from stakeholders, trade-offs, stakeholder engagement, setting-up of completion criteria (balanced scorecard for regional mine closure), targeted research and data management. This paper is a follow-up on work reported.